THE RELATIONSHIP OF GOOGLE CLASSROOM-BASED ONLINE LEARNING WITH STUDENTS' LEARNING MOTIVATION AT STIKES SANTA ELISABETH MEDAN DURING THE COVID-19 PANDEMIC - Vina Yolanda Sari Sigalingging; Ice Septriani Saragih (Jurnal Scientia, 2022)
The purpose of this study is to identify the relationship between online learning based on google classroom and the learning motivation of STIKes Santa Elisabeth Medan students during the COVID-19 pandemic. The research design used by the researcher is correlational. The sample in this study were 114 respondents, and the sampling technique in this study was total sampling. The measuring instrument is in the form of a questionnaire. Data analysis was performed using the Chi-square test. The results showed that Google Classroom-Based Online Learning was less effective (64%) and student learning motivation was quite good (55.3%). Based on the Chi-square statistical test, p value = 0.000 (<0.05), it is concluded that there is a relationship between Google Classroom-Based Online Learning and learning motivation at STIKes Santa Elisabeth Medan during the 2021 Covid-19 Pandemic Period. It is hoped that students can improve the online learning process based on online by using google classroom, WhatsApp, google meeting, Edlink, zoom, and Edmodo so that online learning can be further enhanced in online learning motivation.